2010
DOI: 10.1002/ange.200906994
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(I)‐Catalyzed Intramolecular [5+2] Cycloaddition Reactions of Alkynes and Allenylcyclopropanes: Construction of Bicyclo[5.4.0]undecatrienes and Bicyclo[5.5.0]dodecatrienes

Abstract: Highly strained cyclopropane derivatives have served as useful and powerful C 3 building blocks [1] for the construction of various ring systems, and the metal-catalyzed cleavage of the activated carbon-carbon s bond of the cyclopropane ring [2,3] [3c,g,j] This method [3,4] was successfully applied to the [5+2] cycloaddition reactions of allenes [3e,f,h] as well as alkenes [3b,d,g,j, 4a] as an alternative carbon-carbon p-counterpart. In sharp contrast to the extensive investigation of vinylcyclopropanes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…[2,13] The cyclobutane ring of the intermediate B is opened by a b-carbon elimination, [1,3] which releases the ring strain to generate the nine-membered intermediate C; the reductive elimination of which would result in the formation of 3 a. On the other bond of E into the triple bond leading to the intermediate C. [14][15][16] The previously reported Rh I -catalyzed [5+2] cycloaddition of alkyne-allenylcyclopropane [7] produced cyclopentenylidene derivatives F (n = 1) as a byproduct which would strongly rationalize this pathway (A!E!C). However, in the case of 1 a, the corresponding cyclohexenylidene derivative F (n = 2) could not be detected.…”
Section: Entries 4-7) [Rhcl-mentioning
confidence: 98%
See 1 more Smart Citation
“…[2,13] The cyclobutane ring of the intermediate B is opened by a b-carbon elimination, [1,3] which releases the ring strain to generate the nine-membered intermediate C; the reductive elimination of which would result in the formation of 3 a. On the other bond of E into the triple bond leading to the intermediate C. [14][15][16] The previously reported Rh I -catalyzed [5+2] cycloaddition of alkyne-allenylcyclopropane [7] produced cyclopentenylidene derivatives F (n = 1) as a byproduct which would strongly rationalize this pathway (A!E!C). However, in the case of 1 a, the corresponding cyclohexenylidene derivative F (n = 2) could not be detected.…”
Section: Entries 4-7) [Rhcl-mentioning
confidence: 98%
“…On the other hand, we recently reported that the rhodi-A C H T U N G T R E N N U N G um(I)-catalyzed cycloisomerization of alkyne-allenylcyclopropanes 1 (n = 1) effected the [5+2] ring-forming reaction [7] under rather milder conditions to afford the bicyclic sevenmembered compounds 2 (n = 1, Scheme 1). Based on the easy cleavage of the unfunctionalized cyclopropane ring that was activated by the adjacent allenyl moiety, we next postulated that the replacement of the highly strained allenylcyclopropane by the strained allenylcyclobutane might still give rise to the facile formation of the one-carbon homologated bicyclic eight-membered rings 3 (n = 2, Scheme 1).…”
mentioning
confidence: 98%
“…

Upon exposure to ac atalytic amount of [RhCl-(CO) 2 ] 2 in 1,4-dioxane,h omopropargylallene-alkynes underwent anovel cycloisomerization accompanied by the migration of the alkyne moiety of the homopropargyl functional group to produce six/five/five tricyclic compounds in good yields.A plausible mechanism was proposed on the basis of an experiment with 13 C-labeled substrate.T he resulting tricyclic derivatives were further converted into the corresponding bicyclo-[3.3.0] skeletons with vicinal cis dihydroxyg roups.

Transition-metal-catalyzed cyclization reactions involving CÀH [1] and/or CÀC [2] bond activation steps have emerged as one of the most powerful and straightforward methods in terms of step economy for the construction of complex polycyclic frameworks.O ur recent endeavors in this field focused on the utilization of the inherent properties of the allene functional group [3] in the presence of additional p-components under rhodium catalysis as summarized in Scheme 1. [4,5] These novel rhodium-catalyzed cycloisomerization reactions of allenynes 1 [6] were tentatively surmised to proceed via the initial formation of the plausible rhodabicyclo[4.3.0] intermediates A,w hich should subse-quently collapse through several steps to various types of final products 2-6. [4,7] As af urther utilization of intermediate A,w ee nvisaged that allene-alkyne derivatives 7,with ahomopropargyl group, would produce benzocyclobutene derivatives 8 if it reacted in ap rocess similar to the conversion of 1c into 6 via intermediates A' ' and B (Scheme 2).

Our initial study was carried out using 9,with adimethyl group at the allenic position to avoid unfavorable b-hydride elimination.

…”
mentioning
confidence: 99%
“…[4,5] These novel rhodium-catalyzed cycloisomerization reactions of allenynes 1 [6] were tentatively surmised to proceed via the initial formation of the plausible rhodabicyclo[4.3.0] intermediates A,w hich should subse-quently collapse through several steps to various types of final products 2-6. [4,7] As af urther utilization of intermediate A,w ee nvisaged that allene-alkyne derivatives 7,with ahomopropargyl group, would produce benzocyclobutene derivatives 8 if it reacted in ap rocess similar to the conversion of 1c into 6 via intermediates A' ' and B (Scheme 2).Our initial study was carried out using 9,with adimethyl group at the allenic position to avoid unfavorable b-hydride elimination. [8] Thus as olution of 9a (R 1 = R 2 = Me) in 1,4dioxane was heated at 80 8 8Ci nt he presence of 10 mol %o f [RhCl(CO) 2 ] 2 .T he reaction reached completion within 10 min to provide the unexpected six/five/five tricyclic compound 10 a (R 1 = R 2 = Me) in 90 %y ield (Table 1, entry 1).…”
mentioning
confidence: 99%
“…[1] One of the powerful methods for synthesis of sevenmembered rings is the transition metal catalyzed [5+ +2] reaction [2] between vinylcyclopropanes (VCPs) and 2p-systems. [5a] Since then, the cycloadditions were further developed by Wender et al and many other groups [5][6][7] and the p-systems were expanded to alkenes [8,9] and allenes. [5a] Since then, the cycloadditions were further developed by Wender et al and many other groups [5][6][7] and the p-systems were expanded to alkenes [8,9] and allenes.…”
mentioning
confidence: 99%